Islam’s Universality and the Risale-i Nur’s Method of Interpreting the Qur’an’s Universality - Resid Haylamaz (Universitas Darussalam Gontor, 2014)
Religion came together with the first man as a way of life, making it impossible to separate them. For to do so is opposed to the innate nature of things and gives rise to numerous complications for both the individual and society. As is shown by the purpose of the universe’s creation looking to man and everything being centered on him, and the things told him by the book of the universe being supported by the scriptures, which are all essentially the same differing only in secondary matters, and instructors being sent to expound both ‘books’ and to hasten to man’s assistance - as is shown by these, in consequence of God’s mercy, every age He has called men to a religion-centered way of life, and He continues to do so. It is clear that Islam tried to throw light on in a general sort of way, is a universal message addressing all peoples and all ages. The subjects and general principles it comprises are sufficiently extensive to demonstrate this aspect of it. For it is universal not only in its primary source, the Qur’an, but also in Hadiths, which are based on revelation, and in the general principles derived from these two sources. The Risale-i Nur, one of the most important interpretations of Islam in modern times, lays considerable emphasis on Islam’s universality, stressing particularly that contrarily to what is supposed. Just as the universe is sufficiently comprehensive to satisfy everyone, so the universal message possesses the same breadth and vitality and may address all minds and satisfy them; contrarily to other speech, it neglects nothing. Thus, this paper tried to describe the Risale-I Nur’s Method of Interpreting the Qur’an on Islamic Universality.